2009
DOI: 10.1063/1.3075581
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion induced surface modification for tailoring coercivity in Fe–Ni based amorphous thin films

Abstract: Fe–Ni based amorphous thin films were prepared by thermal evaporation. These films were irradiated by 108 MeV Ag8+ ions at room temperature with fluences ranging from 1×1012 to 3×1013 ions/cm2 using a 15 UD Pelletron accelerator. Glancing angle x-ray diffraction studies showed that the irradiated films retain their amorphous nature. The topographical evolution of the films under swift heavy ion (SHI) bombardment was probed using atomic force microscope and it was noticed that surface roughening was taking plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…The R rms roughness of the as-deposited Zr surface was low at a value of 1.6 nm. This was observed to remain constant after irradiating at fluence of 5×10 12 ions/cm 2 and then increase after 1×10 13 and 5×10 The reduction in granule size could be due to the sputtering of surface structures as a result of multiple ion impacts on the surface and smoothening induced by material transport during surface diffusion at higher irradiation fluence [15]. …”
Section: Resultsmentioning
confidence: 95%
“…The R rms roughness of the as-deposited Zr surface was low at a value of 1.6 nm. This was observed to remain constant after irradiating at fluence of 5×10 12 ions/cm 2 and then increase after 1×10 13 and 5×10 The reduction in granule size could be due to the sputtering of surface structures as a result of multiple ion impacts on the surface and smoothening induced by material transport during surface diffusion at higher irradiation fluence [15]. …”
Section: Resultsmentioning
confidence: 95%
“…The electronic energy loss for SHI is, generally, about two orders of magnitude higher than the nuclear energy loss [13]. SHIs during its passage through material can cause defect annealing, cluster of point defects and columnar type of defects, phase transformation and intermixing at the interfaces [14] depending on the mass and energy of the ion and the material. Therefore, SHIs can be used for engineering the defects in the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Senoy et al and Hysen et al reported the fabrication of thin films from composite targets using vacuum evaporation [19,20]. They also studied annealing and swift heavy ion irradiation effects on these films and reported the formation of Fe-Ni nanocrystals with annealing [21,22]. These nanocrystalline structures precipitate after annealing at 400°C.…”
mentioning
confidence: 99%